2011
DOI: 10.1055/s-0031-1281753
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Gastroschisis: A Comparison of Second vs. Third-Trimester Bowel Dilatation for Predicting Bowel Atresia and Neonatal Outcomes

Abstract: Fetuses with isolated gastroschisis successfully underwent postnatal surgery in most cases (93.2 %), except for one termination, one intrauterine death and 3 cases of neonatal death. A fetal bowel dilatation > 10 mm before 30 + 0 weeks had the highest predictive value for postnatal bowel complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…The predictive value for adverse perinatal outcome of different thresholds of bowel dilatation at the last prenatal ultrasound has been previously studied [16,26,27,28,29,30,31,32,33,34,35]. Controversially, Page et al [36] in a recent systematic review concluded that IABD seen on an antenatal ultrasound scan is not a finding associated with an increased risk of adverse perinatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The predictive value for adverse perinatal outcome of different thresholds of bowel dilatation at the last prenatal ultrasound has been previously studied [16,26,27,28,29,30,31,32,33,34,35]. Controversially, Page et al [36] in a recent systematic review concluded that IABD seen on an antenatal ultrasound scan is not a finding associated with an increased risk of adverse perinatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Because congenital gastrointestinal abnormalities often require surgical correction during the neonatal period, there have been numerous efforts to identify prenatal sonographic findings that predict neonatal outcomes in patients with gastrointestinal anomalies. [9][10][11][12][13][14] Severe bowel dilatation seemed to be associated with poor postnatal outcomes in patients with gastroschisis, 15,16 whereas a dilated bowel and polyhydramnios showed no association with neonatal outcomes in jejunal and ileal atresia. 10,17 Regarding congenital duodenal obstruction, no reported study has focused on prenatal sonographic findings, including bowel dilatation, which could aid in the prediction of adverse outcomes.…”
mentioning
confidence: 98%
“…Intestinal malformations of the fetus lead to obstruction of amniotic fluid swallowing, so such fetuses are prone to polyhydramnios [17,18] . It also suggests that according to the position of fetal intestinal dilation, the occurrence of adverse pregnancy outcomes in pregnant women can be targeted, which is collaborated by previous studies that fetuses with bowel dilatation detected prenatally possess a greater odd of poor prognosis than normal fetuses [19][20][21] .…”
Section: Resultsmentioning
confidence: 80%